The study on cassava properties as gel polymer electrolyte in zinc-air battery - Mohamad Zahid, Abdul Rahman (2018)
The present work investigates the characterization of cassava as gel polymer electrolyte (GPE) in Zinc-air (Zn-air) battery. The use of application energy storage such as battery are important due their speciality including energy renewable, emergency power supply and portable energy. However, most of them are not biodegradable and harmful environmentally. It also face the problem of leakage that might affect short the life cycle of battery. To overcome the problem, cassava GPE with additional potassium hydroxide (KOH) are most suitable material due to biodegradable, difficult to leakage and have high conductivity value. Preparation cassava GPE started by mixing 1 g of cassava powder into 20 mL deionized water. The mixture was heated at 70 °C — 80 °C and stirred until gelling form present. The cassava gel then mixed with different KOH concentration forming cassava GPE. The ionic conductivity, viscoelastic and window stability were evaluated using varying cassava amount and KOH concentration. Conductivity value of pure cassava gel increase drastically after adding KOH solution. The highest ionic conductivity of cassava GPE recorded was at 6 M KOH. The viscosity of cassava GPE was remain constant and does not shown high different in value as the concentration KOH was increased from 2 to 8 M. The highest potential window and the wider stability of anode and cathode region recorder at 6 M KOH. The optimum compositions imbedded in Zn-air battery system are at 6 M KOH.